The impact of scoring weights on price and quality outcomes: An application to the procurement of welfare-to-work contracts - Pierre Koning; Arthur van de Meerendonk (Institute for the Study of Labor (IZA), 2012)
This paper assesses the effects of changes in scoring weights in auctions, using a unique sample of biddings of private Welfare-to-Work (WTW) organizations to reintegrate groups of unemployed and disabled workers. WTW-organizations did not only bid on prices, but also received points for three proxies of the quality of their services: their reputation, a description of their intended methodology to reintegrate workers and the fraction of job placements they considered likely to achieve. We exploit the fact that the scoring weights of these items changed in the time period under consideration, while the broad classification of ('gross') worker types remained similar over time. Our estimation results show that increases in the scoring weights of the quality items result in higher price bids, particularly of WTW-firms that are bidding for the first time as entrants. For the WTW-firms that won the procurements, we find a higher weight for both the reputation and the methodology item to contribute to the job placement of workers.
Keywords: D44; I38; 330; scoring auctions; welfare-to-work; Öffentliche Beschaffung; Auktion; Personalberatung; Aktivierende Sozialhilfe; Qualitatives Verfahren; Dienstleistungsqualität; Niederlande